Impact of Carbapenem Peri-Transplant Prophylaxis and Risk of Extended-Spectrum Cephalosporin-Resistant Enterobacterales Early Urinary Tract Infection in Kidney Transplant Recipients: A Propensity Score-Matched Analysis - Aramwittayanukul, Suwadee; Malathum, Kumthorn; Kantachuvesiri, Surasak; Arpornsujaritkun, Nuttapon; Chootip, Patumsri; Bruminhent, Jackrapong (Frontiers in Medicine, 2022)
Background: Urinary tract infection (UTI) is the most common bacterial infection after kidney transplantation (KT), leading to unfavorable clinical and allograft outcomes. Gram-negative uropathogenic bacteria are frequently encountered especially extended-spectrum cephalosporin-resistant (ESC-R) Enterobacterales (EB), causing UTI early after KT. Methods: A retrospective single transplant study was conducted between January 2016 and December 2019. We performed 1:1 nearest-neighbor propensity score matching without replacement using recipient age, recipient sex, induction, transplant year, human leukocyte antigen, cold ischemia time, and panel-reactive antibody before analyses. Cumulative incidence of ESC-R EB early (within 14 days after KT) UTI was estimated by the Kaplan–Meier method. Risk factors for ESC-R EB early UTI were analyzed by a Cox proportional hazards model. Variables measured after transplantation were considered time-dependent covariates. Results: We included 620 KT recipients (37% women; mean age ± SD, 43 ± 11 years). Overall, 64% and 76% received deceased-donor allograft and induction therapy. Sixty-five (10%) and 555 (90%) received carbapenems and cefuroxime peri-transplant prophylaxis, respectively. Early UTI occurred in 183 (30%) patients, 52% caused by ESC-R EB. Propensity score matching produced 65 well-balanced pairs. During a 14-day follow-up, the cumulative incidence of ESC-R EB early UTI was 5% and 28% in the carbapenems and cefuroxime groups, respectively (log-rank test = 0.003). Peri-transplant carbapenems prophylaxis was a protective factor against ESC-R EB after KT (hazard ratio, 0.19; 95% confidence interval, 0.05–0.64; p = 0.008). Clinical and allograft outcomes did not differ significantly between the groups. Conclusions: In the setting where ESC-R EB UTI is common among KT recipients, carbapenems peri-transplant prophylaxis could protect against the occurrence of early ESC-R EB UTI after KT. Further prospective studies should focus on this specific infection prevention strategy.